Membaca Sisi Lain Keberadaan Angkringan di Kota Denpasar - Sitanggang, Reza Arianto; Kamajaya, Gede; Kebayantini, Ni Luh Nyoman; Sukma Pramestisari, Nyoman Ayu (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This research seeks to examine angkringan as a public space which is seen from the reasons why people are interested in coming to angkringan and various activities that usually take place in angkringan Denpasar City. The approach used in this study is a qualitative approach with an explanatory type of descriptive research. The theory used to analyze this research is the public space of Jurgen Habermas. According to Jurgen Habermas, public space is a place for people to gather and communicate ideas, views, and information. Angkringan, which was originally a place to enjoy food and drinks, has now developed into a space for visitors to gather and interact to discuss ideas, ideas, and information. The results of this study explained that visitors who come to angkringan feel a simplicity but still in a comfortable and relaxed atmosphere. Angkringan is also used as a space for visitors to express and talk about opinions or aspirations about social, political, and economic. In addition, the talks and interactions that are established in the angkringan are free in the absence of binding institutions.   Keywords: Angkringan, Public Space